Analisis Penguasaan Present Tense Mahasiswa Semester 1 Program Studi Agriteknologi Tahun Akademik 2024/2025 - Mayekti, Meilina Haris; Faiza, Dinar; Bestari, Ade Christanty Yudha (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
The research titled "An Analysis of Present Tense Mastery Reflected in the Writings of First-Semester Students of the Agrotechnology Study Program in the Academic Year 2024/2025" aims to determine the extent to which Agrotechnology students understand sentence structure concepts. This is a descriptive study involving a population of 15 students enrolled in the Agrotechnology Study Program for the 2024/2025 academic year. All 15 students were used as the sample in this study. The data were collected through a writing test conducted during the mid-semester examination. In this study, the researcher analyzed all student writing samples, focusing on three main aspects: (1) the presence or absence of present tense verbs as predicates in verbal sentences, (2) the agreement between the predicate and its subject in present tense constructions, and (3) the correct or incorrect use of auxiliary verbs in nominal present tense sentences. The analysis revealed that 95.54% of the student’s demonstrated awareness of using present tense verbs as predicates in the sentences they wrote. Furthermore, 92.69% of the students correctly used present tense predicate forms that matched the subjects of their sentences. Additionally, 92.36% of the students were able to use auxiliary verbs correctly as present tense predicates in nominal sentences. Keywords: present, tense, writing, Agrotechnology